The Determinants Factors of Quality of the Financial Report - Timalsina, Dhanishor; Poudel-Chhetri, Chandra (Bhairahawa Campus Journal, 2023)
This research’s main objective is to find the determinants factors of quality of the financial report prepared by the organization. Quality of the financial report was examined with the support of relevance, faithful representation, comparability, understandability and timeliness. Five hypotheses were developed based on the study's aims to determine the degree of association between the variables. This study was conducted with the primary data. Data are collected through 250 respondents. Respondents for the research purpose were Chartered Accountant, Registered Accountant, Account teacher of various levels and the person working in different post of accountant. Collected data were analyzed by using SPSS-22. The major statistical tools used for the research purpose are reliability analysis, descriptive analysis, correlation analysis and regression analysis. The findings also show that respondents believed timeliness of financial reporting had a greater chance of improving quality of the financial report. Timeliness has moderate positive correlation with the quality of the financial report where as other variable relevance, faithful representation, comparability and understandability has weak positive correlation with quality of the financial report. From this study it can be concluded that relevance, faithful representation, comparability, and understandability have a weak positive link, while timeliness has a moderate positive correlation with financial report quality.